Fabrication methods and applications of microstructured gallium based liquid metal alloys - Khondoker, M A H; Sameoto, D (Smart materials and structures, 2016)
This review contains a comparative study of reported fabrication techniques of gallium based liquid metal alloys embedded in elastomers such as polydimethylsiloxane or other rubbers as well as the primary challenges associated with their use. The eutectic gallium-indium binary alloy (EGaIn) and gallium-indium-tin ternary alloy (galinstan) are the most common non-toxic liquid metals in use today. Due to their deformability, non-toxicity and superior electrical conductivity, these alloys have become very popular among researchers for flexible and reconfigurable electronics applications. All the available manufacturing techniques have been grouped into four major classes. Among them, casting by needle injection is the most widely used technique as it is capable of producing features as small as 150 nm width by high-pressure infiltration. One particular fabrication challenge with gallium based liquid metals is that an oxide skin is rapidly formed on the entire exposed surface. This oxide skin increases wettability on many surfaces, which is excellent for keeping patterned metal in position, but is a drawback in applications like reconfigurable circuits, where the position of liquid metal needs to be altered and controlled accurately. The major challenges involved in many applications of liquid metal alloys have also been discussed thoroughly in this article.